ANALISIS PERLINDUNGAN HUKUM TERHADAP KORBAN PENYEBARAN BERITA BOHONG MELALUI MEDIA SOSIAL FACEBOOK - Tiara Puspita Sari; Serlika Aprita; Susiana Kifli (Sriwijaya Journal of Private Law, 2024)
The widespread circulation of fake news can have a bad impact on the development of the Indonesian state. Fake news can cause arguments and even end friendships. Moreover, fake news contains ethnicity, religion, race and inter-group (SARA) which are very vulnerable to inviting friction between communities, disrupting state stability and diversity. Apart from having a crime aspect (perpetrator of crime), fake news also has a crime victim aspect. Victims in various fake news cases in Indonesia have not received more attention, even though this is an important matter in Indonesian law enforcement. The aim of this research is to find out and explain legal protection for victims of spreading fake news on social media (Facebook), and also the legal efforts that can be taken by victims of spreading fake news on social media (Facebook). The type of legal research that is carried out normatively is where law is conceptualized as what is written in statutory regulations (law in the books) or law is conceptualized as rules or norms which are benchmarks for human behavior that is considered appropriate. Based on the research results, it is understood that legal protection for victims of spreading fake news on social media (Facebook) means that victims receive legal protection from the Witness and Victim Protection Agency (LPSK) in the form of medical assistance, psychological rehabilitation, psychosocial rehabilitation, post-traumatic psychological recovery, compensation/ compensation, restitution. Legal remedies that can be taken by victims of spreading fake news on social media (Facebook) are reporting the incident to the authorities, asking for protection from the Witness and Victim Protection Agency (LPSK), retaliation through criminal or civil law.